"It's All About How You Carry Yourself About": How Medical Students Conceptualize Professionalism in Trinidad & Tobago. Issue 4 (1st October 2016) - Youssef, Valerie C.; Peters, Dexnell; Youssef, Farid F.
ABSTRACT: Phenomenon : This paper concerns itself with the value system that informs and motivates medical students of the twenty-first century as distinct from earlier cohorts. It notes a shift from an era of altruism within which the medical professional was a 'pillar of society' always 'on duty' and always concerned foremost for the patient to an era in which he/she is just another member of the work force, subject to public scrutiny and criticism, to patient autonomy and to a self-serving ethos which characterizes the present age. Whilst concerns have been raised for a continuing and separate morality of medicine, young professionals in other studies have cited a range of characteristics including honesty, trustworthiness and respect alongside competence and medical skill. However, the notion of 'performance' has made a strong thrust into the literature, with students citing the putting on and taking off of dual personae as part of their complex identity in this present time. They are entitled to their own lives, to drop the act and just be themselves when off duty, picking it back up again with the duty call. Approach : The present study then investigated the views on this subject of two groups of medical students in Trinidad & Tobago in the Caribbean, one made up entirely of nationals and one including students from other parts of the Caribbean and the USA. They discussed the topic in focus groups of eight; their responses were then analysed thematically and subject to discourse analysis. Findings : The study revealed diverse attitudes with some embracing the ethical standards of a high calling that whilst others were concerned that too much was expected, that they had a right to break free and be themselves as long as they did not transgress too far from their expected roles. There were two distinct groups both concerned with 'how' they 'carried themselves about' but this meant different things to each dependent on which of the two perspectives they embraced. As a whole, the study revealed an ongoing conflict of value systems with concern for patient welfare just remaining uppermost. Insights : As The University of the West Indies has now stepped into the field of medical professionalism actively it would hope to support students in resolving their conflicts more consciously in response to the range of philosophical stances which currently present themselves.